Secure Infant-Mother Attachment Buffers the Effect of Early-Life Stress on Age of Menarche. (May 2016) - Sung, Sooyeon; Simpson, Jeffry A.; Griskevicius, Vladas; Kuo, Sally I-Chun; Schlomer, Gabriel L.; Belsky, Jay
Prior research indicates that being reared in stressful environments is associated with earlier onset of menarche in girls. In this research, we examined (a) whether these effects are driven by exposure to certain dimensions of stress (harshness or unpredictability) during the first 5 years of life and (b) whether the negative effects of stress on the timing of menarche are buffered by secure infant-mother attachment. Results revealed that (a) exposure to greater harshness (but not unpredictability) during the first 5 years of life predicted earlier menarche and (b) secure infant-mother attachment buffered girls from this effect of harsh environments. By connecting attachment research to its evolutionary foundations, these results illuminate how environmental stressors and relationships early in life jointly affect pubertal timing.